Does the orbitofrontal cortex signal value? - Schoenbaum, Geoffrey (2011)
The orbitofrontal cortex (OFC) has long been implicated in associative learning. Early work by Mishkin and Rolls showed that the OFC was critical for rapid changes in learned behavior, a role that was reflected in the encoding of associative information by orbitofrontal neurons. Over the years, new data—particularly neurophysiological data—have increasingly emphasized the OFC in signaling actual value. These signals have been reported to vary according to internal preferences and judgments and to even be completely independent of the sensory qualities of predictive cues, the actual rewards, and the responses required to obtain them. At the same time, increasingly sophisticated behavioral studies have shown that the OFC is often unnecessary for simple value-based behavior and instead seems critical when information about specific outcomes must be used to guide behavior and learning. Here, we review these data and suggest a theory that potentially reconciles these two ideas, value versus specific outcomes, and bodies of work on the OFC.